1983
DOI: 10.1007/bf00048969
|View full text |Cite
|
Sign up to set email alerts
|

Host resistance to metastasis from mouse mammary carcinomas

Abstract: Although undisturbed primary mouse mammary tumors may give rise to overt metastases, these have generally been observed near the terminal stage of progressive tumor growth. Unlike malignant breast disease in women, metastases are seldom the cause of death in mice, and in some strains as few as 2% of mammary tumor hosts may be affected (1). Highly metastatic tumors may, of course, be found, and hosts of the mammary carcinoma WHT all develop metastases (2). Evidence from animal models suggests that host defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Second, the tumors from both founders strongly express the mutant Met transgene. Third, mammary carcinoma is the predominant form of malignancy found in female transgenic mice expressing the Tpr-Met oncogene (13), or HGF͞SF (12) neither of those reports mentions the presence of metastasis, the metastatic spread of murine mammary carcinoma has been observed previously (31,32). Although the incidence of metastasis from murine mammary carcinoma often is quite low, systems have been described in which mammary tumors are metastatic (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the tumors from both founders strongly express the mutant Met transgene. Third, mammary carcinoma is the predominant form of malignancy found in female transgenic mice expressing the Tpr-Met oncogene (13), or HGF͞SF (12) neither of those reports mentions the presence of metastasis, the metastatic spread of murine mammary carcinoma has been observed previously (31,32). Although the incidence of metastasis from murine mammary carcinoma often is quite low, systems have been described in which mammary tumors are metastatic (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any histologic evidence of active penetration of pulmonary vessel walls by mammary carcinoma cells (Figs. 4 and 5) excludes invasiveness as a determining factor in the metastasizing potentials of mouse mammary carcinomas, as previously reported (Vaage and Harlos, 1987). Other investigators have also observed that active invasiveness by carcinomatous cells may not be essential in the metastatic process (Dingemans and Mooi, 1986;Fisher and Fisher, 1967;Wallace et al, 1978).…”
Section: Tumor Growth Ratementioning
confidence: 59%
“…The expected occurrence of spontaneous pulmonary metastases in 2 out of 3 breeding female C3H/He mice with large spontaneous primary mammary carcinomas (Vaage and Harlos, 1987) provided the opportunity to study a large number of randomly selected tumors from their point and time of origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation